HOLISTIC APPROACH TO LEGAL RESEARCH - Levičev, Vitalij (Teisė, 2015)
Holism in its broadest meaning is philosophical-scientific idea that the whole is greater than the sum of its parts. Such interdependently interacting parts are characterised by unique qualities, which cannot be fully understood without referring to the whole. The concept of holism, unfortunately, is often deluded and its understanding is extremely heterogeneous. That is why it is important not only to distinguish holism-related concepts (holism, collectivism, antireductionism, atomism, individualism and reductionism), but also to perceive their interdependency and methodological boundaries. Holistic ideas may be creatively used in legal research in order to perceive thorough knowledge, reach coherent description, offer efficient suggestions and develop precise prognosis. Firstly, it is important to ensure that legal research is open to different legal paradigms. The methodological-theoretical foundations of the legal science should be continuously revised and amended. Secondly, object of research is indeterminist, complex, hardly predictable and constitutes controlled dynamic system which is inseparably connected with its context and is scholar-dependent. In order to minimize the influence of subjective factors, each researcher should identify her/his subjectivity as clearly as possible. Thirdly, at least three cognizable aspects of legal reality can be distinguished: formal law, real law and ideal law. They are closely interrelated and together constitute the whole picture of legal reality. Fourthly, the whole is in its every component part and vice versa. The research of separate elements is significant in such extent as it can be integrated in the context of overall system. Finally, the methodological synthesis of legal research consists of at least three methodological branches: doctrinal research of formal law, socio-legal research of real law and axiological-ethical research of ideal law. The thorough research of legal reality should include all three of them.